Precambriam Organic Compounds from the Ketilidian of South-West Greenland, Part IV. - Lam, Jørgen; Raunsgaard Pedersen, K. (Meddelelser om Grønland, 1972)
Organic compounds have been extracted from Ketilidian sedimentary rocks (nearly 2000 m.y. old). The results are compared with the previously published data obtained on material from the Ketilidian low metamorphic (greenschist facies ) supracrustals and with results from graphite from the Nagssugtoqidian fold belt of ·west Greenland. Organic compounds have been extracted from two dolomitic samples and a graphite sample of respectively about 15 kg, ? kg, and 8.5 kg. A grey dolomitic shale is the only dolomitic sample in which monoterpenoid compounds were found, and it is different from the others in the lack of normal alkanes, or at least they are present only in trace amounts. A dark dolomitic sample is shown to contain normal alkanes of the range C11 to C2O and a graphite from a high-grade metamorphic gneiss (amphibolite facies) has a content of normal alkanes (C 14 to C, 8), normal fatty acids from C12 to C, 8 and monounsaturated acids from C, 5 to C10 besides branched C13-, C14-, and C, 5-acids. The three samples contain branched-cyclic, aliphatic compounds and various aromatic substances, especially the homologous benzene, naphthalene, and phenanthrene compounds. The organic compounds extracted from the Ketilidian supracrustals are from graphitic and dolomitic rocks of different types deposited under rather different conditions. By comparison it is seen that low-grade metamorphosed samples yield the highest amounts of organic material per kilogram, and that monoterpenoids are present preferentially in coal-graphite samples while only one dolomitic sample contains detectable amounts of monoterpenoid compounds. The variation in the accumulation of organic material was perhaps dependent on the rate of production of organic material and/or on the deposition conditions. There was possibly also a difference in the biological activity, perhaps with different types of organisms, depending on other conditions in the area.